Carbon and hydrogen isotope fractionation during aerobic oxidation of short-chain alkanes in experimental incubations of vent fluids. (August 2021) - Chen, Xue-Gang; Schmidt, Mark; Chen, Chun-Lei; Duan, Wei; Jin, Aimin; Chen, Chen-Tung Arthur; Ye, Ying
Highlights: Aerobic oxidation of alkanes was observed in hydrothermal fluids during storage. The residual CH4 shows the highest ever reported δ 13 C of up to +243‰. The ε C for C1, C2, and C3 oxidation were −37.1‰, −14.8‰ and −4.7‰, respectively. The ε H for methane was −281 ± 187‰, while the Λ value was 8.4 ± 4.6. Aerobic oxidation could produce carbon isotope reversal of the residual alkanes. Abstract: Aerobic oxidation of short-chain alkanes was observed in gas samples from the Lutao intertidal hydrothermal vents in Taiwan, during storage at 20 °C for up to 29 months without adding bacterial strains and replenishing substrates. The carbon isotope fractionation factors ( ε C ) of methane (C1 ), ethane (C2 ), and propane (C3 ), were calculated using the Rayleigh fractionation equation to be −37.1 ± 7.5‰, −14.8 ± 4.8‰, and −4.7 ± 5.2‰, respectively. The hydrogen isotope fractionation factor ( ε H ) of methane was determined to be −281 ± 187‰. DNA sequencing of the 16S rRNA gene in the vent fluids suggests that aerobic oxidation is dominated by methanotrophs of the genera Methylomicrobium and Methylophaga, which use the ribulose monophosphate pathway (RuMP). The degrees of isotope fractionation ( ε C and ε H values) herein are larger than previously reported values, possibly due to the limited O2 supply and low abundance of aerobic methane-oxidizing bacteria in the experiments. Since the fractionation factor of methane is higher than those of ethane and propane, the aerobic oxidation of thermogenic or microbial alkanes could produce a carbon isotope reversal, which is frequently noted as a trait of abiotic hydrocarbons. This work demonstrates that in addition to anaerobic microbial oxidation, aerobic oxidation with a low cell density can also produce significant isotope fractionation of alkanes in geological closed/semi-closed environments and open flow reaction systems that are characterized by moderate temperatures and a limited supply of substrates and O2 ; these environments include cold seeps, mud volcanoes, and low-temperature hydrothermal plumes/aquifers/reservoirs.